2019
DOI: 10.1088/1742-6596/1387/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Development of education game media for xii multimedia class students in vocational school

Abstract: According to the results of interviews with teachers it is known that students experience difficulties in understanding action script material. This is because this material has a high level of complexity, it is proven that only 30% of students are able to achieve the learning objectives. This study aims to produce educational game media in terms of the feasibility and effectiveness of the media. The development model used is ADDIE (analyze, design, development, implementation, evaluation). Methods of data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…The research design is shown in Figure 1. The stages of development research, namely the analysis stage, include an analysis of product development consisting of the topic analysis, learning media analysis, and analysis of the physics concepts used in the developed Converter (Kristanto & Mariono, 2019). The design stage is designing a draft of alternative energy teaching media using ocean wave energy as a source of electrical energy in the form of a simple converter and designing a validation sheet for media experts and material experts (Sutadji, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The research design is shown in Figure 1. The stages of development research, namely the analysis stage, include an analysis of product development consisting of the topic analysis, learning media analysis, and analysis of the physics concepts used in the developed Converter (Kristanto & Mariono, 2019). The design stage is designing a draft of alternative energy teaching media using ocean wave energy as a source of electrical energy in the form of a simple converter and designing a validation sheet for media experts and material experts (Sutadji, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…By minimizing difficulties, the students' concentration increases [15]. Furthermore, in the learning process, educational games facilitate themselves by conveying messages and stimulating students' attention, thoughts, interest, and feeling to achieve learning objectives [16]. Exploiting story elements, the educational game offers excitement [17].…”
Section: Jurnal Teknologi Informasi Dan Pendidikanmentioning
confidence: 99%
“…(Mahnun, 2012) menyampaikan bahwa media dapat dikatakan sebagai sarana dalam menyalurkan sebuah pesan atau informasi yang akan ditujukan kepada penerima pesan yang berasal dari sumber pesan tersebut. (Kristanto et al, 2019) menyampaikan bahwa media dapat dikatakan sarana yang berisikan sebuah pesan atau saran yang digunakan untuk menyampaikan pesan tersebut. Penggunaan media dapat membantu pencapaian tujuan dan meningkatkan hasil dalam proses latihan.…”
Section: Hasil Dan Pembahasanunclassified